SYNTHESIS AND ANTI BACTERIAL ACTIVITY OF 2-(4-AMINOPHENYL) BENZIMIDAZOLE BASED PYRAMIDINE DERIVATIVES - KUMARASWAMY GULLAPELLI; MURALI KRISHNA THUPURANI; G.BRAHMESHWARI (International Journal of Pharma and Bio Sciences, 2014)
As a part of systematic investigation of synthesis ,characterization and biological activities of N-(4-(1H-benzo(d)imidazole -2-yl )-2-(4-hydroxy -6-methyl pyramidine -2-yl thio) acetamide have been synthesized from 2-(4-aminophenyl) benzimidazole and 2-mercapto -4-hydroxy -6-methyl pyramidine ,which have been prepared from p-amino benzoic acid and benzene 1,2 diamine and EAA with thiourea. All the synthesized compounds have been characterized by 1HNMR; IR spectral data .The prepared compounds were tested for antibacterial activity.